The Validity of Biology Module for Senior High School on Grade X in Even Semester Based on Critical Thinking Skills - Nor Aqidatul Husna; Muhammad Zaini; Atiek Winarti (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2021)
Biology learning in schools still experiences several problems. The learning process carried out has not optimally fulfilled the demands of the Education Curriculum, including in helping students to have critical thinking skills. Critical thinking skills can be optimized by developing learning modules. This study aims to obtain a valid biology module based on critical thinking skills for SMA/MA students. The module development method uses Tessmer's research and development design model that focuses on formative evaluation. The module developed refers to six kinds of critical thinking skills according to Facione, including interpretation, analysis, evaluation, inference, explanation, and self-regulation. Data obtained from the validity test by three validators. The percentage of expert validation data was then categorized. Data analysis used the descriptive technique.  The biology learning module based on critical thinking skills that were developed as a whole obtained very valid criteria.Abstrak Pembelajaran Biologi di sekolah masih mengalami beberapa permasalahan. Proses pembelajaran yang dilaksanakan belum secara optimal memenuhi tuntutan Kurikulum Pendidikan, diantaranya dalam membantu peserta didik untuk memiliki keterampilan berpikir kritis. Keterampilan berpikir kritis dapat dioptimalkan dengan mengembangkan modul pembelajaran. Tujuan dari penelitian ini adalah untuk mendapatkan modul biologi yang berbasis keterampilan berpikir kritis pada peserta didik SMA/MA yang valid. Metode pengembangan modul menggunakan model desain penelitian pengembangan dari Tessmer yang fokus pada evaluasi formatif. Modul yang dikembangkan mengacu pada enam macam keterampilan berpikir kritis menurut Facione, meliputi interpretasi, analisis, evaluasi, inferensi, eksplanasi dan regulasi diri. Data diperoleh dari uji validitas oleh tiga validator. Persentase data validasi ahli kemudian dikategorisasi. Analisis data menggunakan teknik deskriptif kategorisasi. Modul pembelajaran biologi berbasis keterampilan berpikir kritis yang dikembangkan secara keseluruhan memperoleh kriteria sangat valid.